ESTIMATION OF POLITICAL OLIGOPOLY POWER OF DOMESTIC PRODUCERS IN THE KOREAN RAW-MILK MARKET - 전상곤 (한국농촌경제연구원, 2008)
This paper estimates the political oligopoly power of domestic raw-milk producers in the Korean dairy market. Domestic raw-milk price for fluid use is decided exogenously by the government. The government announces the reference price of raw-milk price for fluid use to protect the domestic raw-milk producers from the potential market power of domestic dairy processors, because historically many small-sized domestic producers are a relatively weaker group than domestic processors. Here, this study has two questions: one is about how effectively the government protects the producers and the other is about how much the producers exert their political power against the government to raise the reference price in this process. Furthermore, this paper also tests how much the political oligopoly power of domestic producers is affected by the change of domestic political situation which is the inauguration of Korea Dairy Committee in this case. To answer these questions, this paper develops a theoretical model from a social welfare function and empirically estimates the political oligopoly power using the new empirical industrial organization (NEIO) approach.
Keywords: Political power; market power; dairy; milk; Political power; market power; dairy; milk